TCP Transcription Factors Interact With NPR1 and Contribute Redundantly to Systemic Acquired Resistance - Li, Min; Chen, Huan; Chen, Jian; Chang, Ming; Palmer, Ian A.; Gassmann, Walter; Liu, Fengquan; Fu, Zheng Qing (Frontiers in Plant Science, 2018)
In Arabidopsis, TEOSINTE BRANCHED 1, CYCLOIDEA, PCF1 (TCP) transcription factors (TF) play critical functions in developmental processes. Recent studies suggest they also function in plant immunity, but whether they play an important role in systemic acquired resistance (SAR) is still unknown. NON-EXPRESSER OF PR GENES 1 (NPR1), as an essential transcriptional regulatory node in SAR, exerts its regulatory role in downstream genes expression through interaction with TFs. In this work, we provide biochemical and genetic evidence that TCP8, TCP14, and TCP15 are involved in the SAR signaling pathway. TCP8, TCP14, and TCP15 physically interacted with NPR1 in yeast two-hybrid assays, and these interactions were further confirmed in vivo. SAR against the infection of virulent strain Pseudomonas syringae pv maculicola (Psm) ES4326 in the triple T-DNA insertion mutant tcp8-1 tcp14-5 tcp15-3 was partially compromised compared with Columbia 0 (Col-0) wild type plants. The induction of SAR marker genes PR1, PR2, and PR5 in local and systemic leaves was dramatically decreased in the tcp8-1 tcp14-5 tcp15-3 mutant compared with that in Col-0 after local treatment with Psm ES4326 carrying avrRpt2. Results from yeast one-hybrid and chromatin immunoprecipitation (ChIP) assays demonstrated that TCP15 can bind to a conserved TCP binding motif, GCGGGAC, within the promoter of PR5, and this binding was enhanced by NPR1. Results from RT-qPCR assays showed that TCP15 promotes the expression of PR5 in response to salicylic acid induction. Taken together, these data reveal that TCP8, TCP14, and TCP15 physically interact with NPR1 and function redundantly to establish SAR, that TCP15 promotes the expression of PR5 through directly binding a TCP binding site within the promoter of PR5, and that this binding is enhanced by NPR1.